Enfermedad diarréica aguda y antibióticos - Pérez-Stable, Manuel; Gómez Riera, Manuel; Fernández, Nora; Fraga, Nieves (Revista Cubana de Pediatría, 2023)
Informa la experiencia en estos enfermos durante 1971.